Antioxidant and Anticancer Activities of Anethum graveolens L., Citrus limon (L.) Osbeck and Zingiber officinale Roscoe Essential Oils - Mahmoud Osanloo; Ali Ghanbariasad; Ali Taghinezhad (Tehran University of Medical Sciences, 2021)
Since synthetic chemotherapeutic drugs produce a certain degree of drug resistance and due to their common side effects, such as damage to hematopoietic cells and hair loss, it is necessary to use herbal medicine as a substrate to develop new anticancer drugs. The ingredients of three essential oils (EO) were identified using gas chromatography-mass spectrometry (GC-MS) analysis. Their anticancer activities have been investigated on four human breast cancer cell lines, including MCF-7, MDA-MB-175, MDA-MB-231, and MDA-MB-468. In addition, their antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The three plants were investigated for identifications of the ingredients of their EOs, and major ingredients were identified in each plant as alpha-phellandrene (26.75 %) in Anethum graveolens L., limonene (61.83 %) in Citrus limon (L.) Osbeck, and zingiberene (30.28 %) in Zingiber officinale Roscoe. Among the EOs, C. limon was significantly more effective than others; its half-maximal inhibitory concentration (IC50) on MCF-7 was obtained at 201 µg.mL-1. Furthermore, Z. officinale EO showed a higher antioxidant activities in comparison to the two other EOs. Considering the antioxidant and anticancer effects of the EOs, they could be further investigated as a possible complementary medicine in cancer.